Role of Pharmacists and Nurses in Preventing Medication-Related Toxicity in High-Risk Patients - Enaam Mohammed Shbaily; Hadeel Mohamed Jaafary; Nasser Jaber Moharraq; Rehab Hadi Alhkallaf; Raneem Sami Alharbi; Bashaer Ahmed Elagi; Ghayah Abdullah Jabbari; Norah Hussain Ali; Aisha Suqir Alsufyani; Eman Ali Alhumayani; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Drug toxicity continues to be one of the significant issues in healthcare. It is, most of the time, responsible for adverse drug events (ADEs), hospitalizations, morbidity, and mortality among high-risk patients. This broad overview considers the significant collaborative roles that pharmacists and nurses play in the prevention of medication-related toxicity in high-risk populations, comprising older adults, individuals with multiple comorbidities, and patients requiring polypharmacy.It describes the integral aspects of pharmacists’ participation in medication therapy management (MTM), clinical pharmacokinetic monitoring, and patient education, as well as nurses’ important roles in medication administration, patient monitoring, and early detection of toxicity.Implementing technological solutions, such as clinical decision support systems (CDSS), barcode medication administration (BCMA), and smart infusion pumps, has improved prevention efforts.Challenges include staffing restraints on care fragmentation and the need for more interprofessional training.This research shows that integrated programs, including pharmacist medication reviews and vigilant nursing clinical monitoring, have reduced error rates by up to 50% in other healthcare settings.Integrating personalized medicine approaches, particularly pharmacogenomics, would ensure potential opportunities to optimize medication safety for high-risk populations.According to this study, successfully preventing medication-related toxicity requires a coordinated, multidisciplinary approach, with ongoing investment in research, technology, and workforce development support.